Review of Big Data Implementation and Expectations in Smart Cities - Yingnan Zhuang; Jeremy Cenci; Jiazhen Zhang (Buildings)
With the construction of smart cities advancing, research on big data and smart cities has become crucial for sustainable development. This study seeks to fill gaps in the literature and elucidate the significance of big data and smart city research, offering a comprehensive analysis that aims to foster academic understanding, promote urban development, and drive technological innovation. Using bibliometric methods and Citespace software (6.2.R3), this study comprehensively examines the research landscape from 2015 to 2023, aiming to understand its dynamics. Under the guidance of the United Nations, global research on big data and smart cities is progressing. Using the Web of Science (WOS) Core Collection as the data source, an exhaustive visual analysis was conducted, revealing various aspects, including the literature output, journal distribution, geographic study trends, research themes, and collaborative networks of scholars and institutions. This study reveals a downward trend despite research growth from 2015 to 2020, focusing on digital technology, smart city innovations, energy management and environmental applications, data security, and sustainable development. However, biases persist towards technology, information silos, homogenised research, and short-sighted strategies. Research should prioritise effectiveness, applications, diverse fields, and interdisciplinary collaboration to advance smart cities comprehensively. In the post-COVID-19 era, using big data to optimise city management is key to fostering intelligent, green, and humane cities and to exploring efficient mechanisms to address urban development challenges in the new era.